PENGATURAN JUMLAH CABANG UTAMA DAN PENJARANGAN BUAH TERHADAP HASIL DAN MUTU BENIH TOMAT VARIETAS KALIURANG (LYCOPERSICUM ESCULENTUM MILL ) - Wartapa, Agus; Effendi, Yoniar; Sukadi, Sukadi (Jurnal Ilmu-Ilmu Pertanian, 2009)
The Research purpose was to study the arrangement of primary branch number and crop reduction on the yield and seed quality of Kaliurang tomato variety. A field experiment was conducted on regosol soil located in Agriculture Extension College Yogyakarta at 115 m above sea level (asl). The experiment was carried out following 3X3 factorial design arranged in Completely Randomized Block Design with 3 replications. The first factor was branch with 3 levels i.e. 1 primary branch, 2 primary branches and 3 primary branches. The second factor was reduction of tomato fruit set consisting 3 levels i.e. 0,96 reduction, 15% reduction and 30% reduction. The results show that 3 primary branch and 15 94, or 30 96 crop reduction best crop growth rate, leaf area index on 6 weeks plant growth. The treatment of 3 primary branches and 15% crop reduction gave the highest tomato yield per hectare. And the best weight of 1000 seeds was obtained front the combination of 1 primary branch with 30 % tomato reduction.